ROLE OF PEOPLE BUSINESS CREDIT PROGRAM TO SUPPORT THE ADVANCEMENT MICRO, SMALL, AND MEDIUM ENTERPRISES IN MALANG (Case Study of Debtor PT. Bank Rakyat Indonesia Subsidiary Branch Office XXX, Malang) - Sabila, Gabriella Shinta (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to know the role of People Business Credit Program to support the advancement Micro, Small, and Medium Enterprises in Malang. People Business Credit Program is financing given from Banking to entrepreneurs that have business prospects and the ability to restore debt on time. The approach used in this research is qualitative with the method of case study. Researchers used non probability sampling by using the purposive sampling method and snowball sampling. The parties that will be used as informants in this research is perpetrators of Micro, Small, and Medium Enterprises asking the People Business Credit Program and Bankers BRI Subsidiary Branch Office XXX, Malang. The results of this study show that the presence of this credit can support the advancement of Micro, Small,  Medium  Enterprises,  because  after  getting  additional  funds  from  banking  the  informants (debtor) can expand business and increase revenue. The recommendations can be given author related to this research is in term of marketing it would be better if the program is more socialized through print and electronic media so that people in urban or rural can obtain information clearly, it would be better if BRI provide waivers by way of freeing up collateral but with tight supervision so more appropriate targets Keywords :Role, Micro, Small, Medium Enterprises, People Business Credit Program, Income